Adherence to Mediterranean diet and risk of prostate cancer. (3rd April 2019) - Urquiza-Salvat, Noelia; Pascual-Geler, Manrique; Lopez-Guarnido, Olga; Rodrigo, Lourdes; Martinez-Burgos, Alba; Cozar, Jose Manuel; Ocaña-Peinado, Francisco Manuel; Álvarez-Cubero, Maria Jesus; Rivas, Ana
Abstract: In Europe, countries following the traditional Mediterranean Diet (MeDi), particularly Southern European countries, have lower prostate cancer (PCa) incidence and mortality compared to other European regions. In the present study, we investigated the association between the MeDi and the relative risk of PCa and tumor aggressiveness in a Spanish population. Among individual score components, it has been found that subjects with PCa were less likely to consume olive oil as the main culinary fat, vegetables, fruits and fish than those without. However, these differences were not statistically significative. A high intake of fruit, vegetables and cooked tomato sauce Mediterranean style (sofrito) was related to less PCa aggressiveness. Results showed that there are no differences in the score of adherence to the Mediterranean dietary patterns between cases and controls, with mean values of 8.37 ± 1.80 and 8.25 ± 2.48, respectively. However, MeDi was associated with lower PCa agressiveness according to Gleason score. Hence, relations between Mediterranean dietary patterns and PCa are still inconclusive and merit further investigations. Further large-scale studies are required to clarify the effect of MeDi on prostate health, in order to establish the role of this diet in the prevention of PCa.